2019
DOI: 10.1002/jcaf.22386
|View full text |Cite
|
Sign up to set email alerts
|

CEO characteristics, accounting opacity and stock price synchronicity: Empirical evidence from German listed firms

Abstract: We examine the influence of accounting opacity (earnings management [EM] and tax aggressiveness [TA]) and CEO characteristics (CEO age and tenure) on stock price synchronicity (SPS) of German companies and we test if CEO age and CEO tenure moderate the relation between EM, TA, and SPS. Using the GLS regression, we find that TA and EM have a significant positive effect on SPS. CEO age negatively moderates the relation between TA and SPS. CEO tenure affects positively SPS, but did not moderate neither the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 54 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…In the data observation, a CEO with a maximum value tenure of 31 years has the maximum discretionary accruals of 0.920. (Neifar & Ajili, 2019) found that CEOs performed earnings management at the end of their tenure years, which increases profits when the CEO retires based on company performance. Furthermore, (Baker et al, 2019) found that CEOs performed earnings management, which increases earnings while approaching the end of retirement to increase the probability of serving on the board of directors when the CEO is entering retirement age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the data observation, a CEO with a maximum value tenure of 31 years has the maximum discretionary accruals of 0.920. (Neifar & Ajili, 2019) found that CEOs performed earnings management at the end of their tenure years, which increases profits when the CEO retires based on company performance. Furthermore, (Baker et al, 2019) found that CEOs performed earnings management, which increases earnings while approaching the end of retirement to increase the probability of serving on the board of directors when the CEO is entering retirement age.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, doing an in-depth study on the role of women on Indonesian boards of directors is a very significant and fascinating issue to do in order to provide references for Indonesian businesses (Leviana et al, 2019). Many previous studies focused on the relationship between CEO characteristics and earnings management in industrialised nations in several sectors (Borgi et al, 2021;Kalkhouran et al, 2017;Neifar & Ajili, 2019). However, (Alqatamin et al, 2017) showed conflicting and unclear evidence regarding how a manager's personal qualities and earning management techniques relate.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, German-speaking CEOs who left office had an average tenure of 6.6 years [9]. In a study of how CEO age and CEO tenure moderates the relation between certain financial factors, Neifar and Ajili [10] determined a tenure of 6.5 years for German CEOs. These figures are consistent with the average tenure of US-American CEOs, which is 6.9 years [3].…”
Section: Literature Review and Hypotheses Buildingmentioning
confidence: 99%
“…The higher the information transparency, the more information about the firm-specific information that investors could collect, thereby reducing the synchronicity of stock prices. Further studies investigate other determinants of stock price synchronicity, such as ownership concentration ( Gul et al, 2010 ), large controlling shareholders ( Boubaker et al, 2014 ), institutional investors ( An and Zhang, 2013 ), analysts ( Jiang et al, 2018 ), and managerial characteristics ( Neifar and Ajili, 2019 ). In emerging markets, the stock price synchronicity is much higher than that of developed markets ( Jin and Myers, 2006 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%